An annotated checklist of the non-marine ostracods (Crustacea) of Algeria with some ecological notes - Ghaouaci, Souad; Yavuzatmaca, Mehmet; Külköylüoğlu, Okan; Amarouayache, Mounia (Zootaxa, 2017)
A total of 47 non-marine ostracods are listed from Algeria including both, the species reported in literature and those collected from 117 water bodies in humid, semi-arid and arid regions of Algeria between 2012 and 2016. Twenty seven taxa were identified with three species (Cypris pubera, Limnocythere inopinata, Potamocypris variegata) new to Algeria and nine taxa (Eucypris kerkyrensis, E. lilljeborgi, Heterocypris rotundata, Ilyocypris decipiens, I. cf. japonica, Isocypris beauchampi, Potamocypris smaragdina, P. villosa, Prionocypris zenkeri) as new reports for North Africa. Considering the presence of highly diverse water bodies, seasonal differences and difficulties of access to water sources, the number of species listed in here is believed to be underestimated. Further studies are required to complete this list.